Beneficial Effects of Intrarosa® (Vaginal Prasterone) on the Vaginal Histology of Women With VVA Treated or not With Aromatase Inhibitors: A Breakthrough in the Understanding of the Role of Androgens in Vaginal Health. (1st August 2022) - Bouchard, C; Ouellet, J; Coté, I; Dumas, M; Dury, A
ABSTRACT: Introduction: The vaginal mucosa relies on a constant turnover of its epithelium to remain healthy. Epithelial parabasal cells divide and fill up with glycogen as they get pushed towards the vaginal lumen. They end up desquamating and releasing glycogen for the resident lactobacilli to feed on and acidify the medium. The stimulation required for this quintessential mechanism to go on has historically been attributed to estrogens, however, growing clinical evidence supports that androgens may play a role. Aromatase inhibitors (AI) are used in breast cancer survivors to completely inhibit the synthesis of estrogens. Administering a steroid precursor such as prasterone (DHEA) to patients suffering from vulvovaginal atrophy (VVA) and taking AI will therefore only result in local synthesis of androgens, but no estrogens. Objective: We set out to compare the histological changes an atrophic vaginal mucosa goes through with prasterone treatment, with and without exclusion of the estrogenic benefits by AI. Methods: A Wittner punch was used to collect biopsies both before and after 12 weeks of treatment with 6.5 mg intravaginal prasterone daily (Intrarosa®). Upon collection, samples were formalin fixed and paraffin embedded for further processing. Morphological assessment of the biopsies was conducted using Masson's trichrome staining. Six menopausal women suffering from VVA and meeting the inclusion criteria were recruited, as well as two breast cancer survivors on AI. Results: The degree of epithelial atrophy visible at baseline histology for VVA patients was variable, but all six patients had the histological characteristics of a thick, healthy epithelium by the end of the study.  At baseline, both patients on aromatase inhibitors had a very thin, flattened epithelium. Following treatment with prasterone and despite the aromatase inhibitors, the epithelium showed striking histological improvements, regaining thickness, ridges and glycogen synthesis. Conclusions: Although there is some level of clinical evidence in the literature suggesting that androgens can help treat symptoms of the genitourinary syndrome of menopause (GSM), data presented here are believed to be the first demonstration of profound beneficial effects of androgens on VVA, independently from estrogens. While further studies are warranted to better understand the respective contributions of androgens and estrogens to the benefits observed with prasterone in the treatment of GSM, the data presented here strongly suggests that androgens play a significant role in the physiopathology of VVA. Disclosure: Yes, this is sponsored by industry/sponsor: Endoceutics